2007
DOI: 10.1152/ajpheart.00998.2007
|View full text |Cite
|
Sign up to set email alerts
|

Dimethylarginine dimethylaminohydrolase (DDAH): expression, regulation, and function in the cardiovascular and renal systems

Abstract: Palm F, Onozato ML, Luo Z, Wilcox CS. Dimethylarginine dimethylaminohydrolase (DDAH): expression, regulation, and function in the cardiovascular and renal systems. Am J Physiol Heart Circ Physiol 293: H3227-H3245, 2007. First published October 12, 2007; doi:10.1152 doi:10. /ajpheart.00998.2007 )-dimethylarginine (ADMA) inhibits nitric oxide (NO) synthases (NOS). ADMA is a risk factor for endothelial dysfunction, cardiovascular mortality, and progression of chronic kidney disease. Two isoforms of dimethylargini… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
301
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 286 publications
(317 citation statements)
references
References 236 publications
9
301
1
Order By: Relevance
“…[1][2][3] In addition to its capacity to promote the occurrence of hypertension by inhibiting vasodilatation, an ADMA-determined reduction of endothelial NO bioavailability could impair its vasoprotective function and thereby contribute to the pathogenesis of both hypertension and atherosclerosis and consequent cardiovascular morbidity and mortality. 30 The current observations suggest that normotensive salt sensitivity accompanied by NaClinduced increase in plasma ADMA might constitute a pathogenic state worthy of preventive intervention, as with supplemental dietary potassium, 27 particularly in those who are potassium deficient, as blacks often are. 36 …”
Section: Perspectivesmentioning
confidence: 80%
See 2 more Smart Citations
“…[1][2][3] In addition to its capacity to promote the occurrence of hypertension by inhibiting vasodilatation, an ADMA-determined reduction of endothelial NO bioavailability could impair its vasoprotective function and thereby contribute to the pathogenesis of both hypertension and atherosclerosis and consequent cardiovascular morbidity and mortality. 30 The current observations suggest that normotensive salt sensitivity accompanied by NaClinduced increase in plasma ADMA might constitute a pathogenic state worthy of preventive intervention, as with supplemental dietary potassium, 27 particularly in those who are potassium deficient, as blacks often are. 36 …”
Section: Perspectivesmentioning
confidence: 80%
“…30,31 O 2 Ϫ scavenges NO, which, by reacting with O 2 Ϫ , is a major endogenous antioxidant. 30,32 Thus, an ADMA-determined decrease in NO formation increases oxidative stress. The increase is self-amplifying in that it can "uncouple" NOS so that it yields not NO but O 2 Ϫ .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…ADMA can be metabolized by DDAH‐1 and DDAH‐2, thereby increasing eNOS‐derived NO bioavailability 19, 20. Thus, DDAH deregulation, which causes ADMA accumulation, is also a risk factor for cardiovascular diseases 19, 20.…”
Section: Discussionmentioning
confidence: 99%
“…PCR and Western blot analysis have revealed that the endothelium contains mRNA and protein for both DDAH-1 and DDAH-2 (8,11,14,15,37,41). However, in order to assess the relative contribution of each enzyme, a detailed analysis of the enzyme kinetics of each isoform is necessary.…”
Section: Discussionmentioning
confidence: 99%